Clinical and material degradations of intraocular lenses: A review. Issue 5 (September 2020) - Stanojcic, Nick; Hull, Christopher; O'Brart, David PS
Purpose: To review the published scientific literature concerning clinical and material degradations of intraocular lenses after implantation in cataract surgery. Methods: A search was undertaken using the following databases: CENTRAL (including Cochrane Eyes and Vision Trials Register; The Cochrane Library: Issue 2 of 12 February 2019), Ovid MEDLINE (R) without Revisions (1996 to February week 2, 2019), Ovid MEDLINE (R) (1946 to February week 2, 2019), Ovid MEDLINE (R) Daily Update 19 February 2019, MEDLINE and MEDLINE non-indexed items, Embase (1980–2019, week 7), Embase (1974–2019, 19 February), Ovid MEDLINE (R) and Epub Ahead of Print, in-Process & Other Non-Indexed Citations and Daily (1946 to 19 February 2019), Web of Science (all years), the meta Register of Controlled Trials ( m RCT) (www.controlled-trials.com ), ClinicalTrials.gov (www.clinicaltrial.gov ) and the WHO International Clinical Trials Registry Platform (www.who.int/ictrp/search/en ). Only published articles in English were selected. Search terms/keywords included 'IOL' or 'intraocular lens', combined with 'opacification', degradation, glistenings, nanoglistenings, whitening, transmittance, light scatter, discolouration/discoloration, performance, quality, material, biocompatibility, calcification, explantation and ultraviolet/UV radiation. Relevant in-article references not returned in our searches were also considered. Results: After review of the available articles, the authors included 122 publications in this review, based on the quality of their methodology and their originality. The studies included in this review were randomized controlled trials, cohort studies, case-controlled studies, case series, case reports, laboratory studies and review papers. Differing material degradations of intraocular lenses have been described and their associated pathophysiology studied. Reported anomalies include photochemical alterations, water vacuoles, internal and surface calcific deposits, surface coatings and discolouration. The nature of such changes has been shown to depend on the type of intraocular lenses material used and/or manufacturing processes and storage conditions employed. Changes in the intraocular lens can also be influenced by surgical technique, coexisting ocular pathologies and topical and systemic medications. The clinical significance of these degradations is variable, with some resulting in significant visual disturbance and the need for intraocular lens explantation and others producing only minimal visual impairments. Failure to recognize the precise nature of the problem may lead to unnecessary laser capsulotomy procedures. Conclusion: Clinical degradations of intraocular lenses are uncommon but have been reported following the implantation of intraocular lenses made of differing biomaterials. Their correct identification and thorough investigation to determine the underlying cause is necessary for optimal patient management and the prevention of such problems. Choosing a lens made of a particular material may be important in patients with certain ocular conditions.